Fiscal and monetary policy in Belgium, France, Germany, Luxembourg, and The Netherlands - Christian Fahrholz; Philipp Mohl (Free University Berlin, Jean Monnet Centre of Excellence, 2003)
This regional input analyses recent developments and future prospects of fiscal policy (part I) and monetary policy (part II) of Benelux, France and Germany (EMU-5) covering the period of 1997-2004. The fiscal policy part concentrates on budgetary effects of the eastward enlargement. Besides, socio-economic developments are considered, as well. In context of monetary policy affairs, the heterogeneity of EMU-5 members is surveyed. The brief analysis of two main aspects of the monetary union the GDP growth rates and the inflation rates indicates that diversity among the surveyed countries still prevails.
Keywords: E5; F4; E61; E65; 330; EU-budget costs; ECB; EMU; EU-enlargement; fiscal and monetary policy; heterogeneity; Stability and Growth Pact